A people's history of the United States - Zinn, Howard, 1922-2010. (New York : Harper Perennial, 2010)
Presents the history of the United States from the point of view of those who were exploited in the name of American progress.
Columbus, the Indians, and human progress -- Drawing the color line -- Persons of mean and vile condition -- Tyranny is tyranny -- A kind of revolution -- The intimately oppressed -- As long as grass grows or water runs -- We take nothing by conquest, thank God -- Slavery without submission, emancipation without freedom -- The other civil war -- Robber barons and rebels -- The empire and the people -- The socialist challenge -- War is the health of the state -- Self-help in hard times -- A people's war? --'Or does it explode?' -- The impossible victory: Vietnam -- Surprises -- The seventies: under control? -- Carter-Reagan-Bush: the bipartisan consensus -- The unreported resistance -- The coming revolt of the guards -- The Clinton presidency -- The 2000 election and the'war on terrorism.' -- Afterword.
Includes bibliographical references (p. [689]-708) and index.
Buku Bacaan Asas Fakulti
Keywords: United States -- History; United States -- History